The spectacular devastation of the bushfire - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Bushfires are an age-old scourge. Even in 2500 BC a Carthaginian king noted in his travel diary the existence of farm-fires in West Africa. In those days and up till quite recently they did not cause too much damage environmentally. Population...